2018
DOI: 10.1136/tsaco-2018-000201
|View full text |Cite
|
Sign up to set email alerts
|

Improving survival after an emergency resuscitative thoracotomy: a 5-year review of the Trauma Quality Improvement Program

Abstract: BackgroundAdvancement in trauma care has led to the evolution of emergency resuscitative thoracotomy (ERT) for the revival of trauma patients. We now have more precise understanding of selecting suitable patients for achieving optimal outcomes. The aim of our study was to analyze the utilization and survival trends during the past 5 years, as well as factors that influence survival after ERT.MethodsA 5-year (2010-2014) analysis of all trauma patients ≥18 years who underwent ERT in the American College of Surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 27 publications
(21 reference statements)
0
17
1
Order By: Relevance
“…The differences in these factors might have largely affected the survival rate observed in the present study (13.0% in the overall study cohort), which was higher than that of previously reported [23][24][25][26]. Joseph et al [27] reviewed patients who underwent exploratory thoracotomy (ICD-9-CM, 34.02) within the first hour of hospital admission using the TQIP database and reported 9.6% survival rate. However, their study included patients without SOL on hospital arrival (28.6% of the analyzed cohort).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The differences in these factors might have largely affected the survival rate observed in the present study (13.0% in the overall study cohort), which was higher than that of previously reported [23][24][25][26]. Joseph et al [27] reviewed patients who underwent exploratory thoracotomy (ICD-9-CM, 34.02) within the first hour of hospital admission using the TQIP database and reported 9.6% survival rate. However, their study included patients without SOL on hospital arrival (28.6% of the analyzed cohort).…”
Section: Discussioncontrasting
confidence: 58%
“…Joseph et al [ 27 ] reviewed patients who underwent exploratory thoracotomy (ICD-9-CM, 34.02) within the first hour of hospital admission using the TQIP database and reported 9.6% survival rate. However, their study included patients without SOL on hospital arrival (28.6% of the analyzed cohort).…”
Section: Discussionmentioning
confidence: 99%
“…2 Second, young age and penetrating injury are favorable factors for an improved neurologic outcome in case of traumatic cardiac arrest. 6 The anatomic location and mechanism of injury are independent predictors of survival. 6 Damage control surgery focuses on resolving life-threatening situations and does not involve complete evaluation of all organs if not directly indicated.…”
Section: Discussionmentioning
confidence: 99%
“…6 The anatomic location and mechanism of injury are independent predictors of survival. 6 Damage control surgery focuses on resolving life-threatening situations and does not involve complete evaluation of all organs if not directly indicated. After damage control surgery, focus shifts to stabilization in the ICU before any other procedures are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…REBOA has recently re-gained popularity as an alternative to resuscitative thoracotomy (RT, thoracotomy and aortic cross-clamping) in trauma patients (28). RT has been associated with low survival rates (9, 10) and presents significant risks of injuries for care providers themselves. Furthermore, while RT may provide hemorrhage control, the thoracotomy itself adds a substantial injury to the patient with considerable recovery time.…”
Section: Introductionmentioning
confidence: 99%